Molecular Review: Effects of Physical Exercise in Skeletal Muscle Glucose Uptake - Rahmi Rahmi (Talenta Publisher, 2021)
Muscle contraction requires glucose as its main fuel. Glucose enters the muscle cells through diffusion facilitated by GLUT4. GLUT4 must be translocated from intracellular to the plasma membrane and T tubules during muscle contraction. This literature review will discuss how physical exercise can signal GLUT4 translocation for glucose uptake. Molecular signals induced by physical exercise are very complex and involve various molecules, one of which is AMPK and intracellular Ca concentration.